Fan Fiction as Phenomenon of Modern Literature: Case of “Eugene Onegin” - R. O. Raynkhardt (Научный диалог)
Fan fiction as a modern literary phenomenon with deep historical roots is considered on the example of the recently published work “Eugene Onegin. 2.0 Version. Experiment in verse” by Alina Sakhnenko (2014). The basic principles of the construction of works in the genre of fan fiction, as well as the relationship between the latter and literary parody are described. By the example of Alina Sakhnenko’s work the newest tendencies of development of this direction in the Russian poetry are illustrated. The analysis is made of characteristic stylistic techniques used by the author, in particular, reminiscences of the original work by A. S. Pushkin, along with a comparison of the relevant storylines. According to the results of the analysis, it is concluded that the studied fan fiction, remaining a parody in form, not devoid of significant stylistic shortcomings in terms of rhythm and rhyme, is a valuable material describing the domestic realities of the 2010-ies. The author of the article claims that this fan fiction text contains the cultural code of a whole generation of people born and raised in Russia in the 1990-ies.